Karakteristik anak yang mengalami child abuse dan neglect di RSUP Sanglah, Denpasar, Indonesia tahun 2015-2017 - Made Ardinata; Soetjiningsih Soetjiningsih; I Gusti Ayu Trisna Windiani; I Gusti Agung Ngurah Sugitha Adnyana; Ida Bagus Putu Alit (Intisari Sains Medis, 2019)
Background: Child abuse and neglect is any form of physical, emotional, sexual abuse, or neglect of children. Child abuse causes various consequences that are harmful to the child and the future of the nation. The purpose of this study was to determine the characteristics of children who experience child abuse at Sanglah Hospital Denpasar.Methods: A cross sectional study design was conducted using secondary data taken from medical records of the Forensic Medicine Department, Sanglah General Hospital Denpasar from January 2015 to December 2017. Data related to age, gender, origin, types of abuse, and perpetrator’s house were analyzed as percentage using SPSS version 17 software. Ethical clearance was carried out prior study conducted. Result: From 2015 to 2017, 173 subjects were recorded as child abuse. The age group of 13-15 years and 16-18 years is the highest age group that experiences child abuse which is 28.3% and 33.5%. Subjects of female sex were 56.0%. The highest distribution of subject origin comes from Denpasar area 20.8% and the highest education level of parents is 45.0% senior high school. Subjects who experienced physical violence and threats were 93.6%, sexual violence was 50.8%, and 1.7% experienced neglect. The perpetrators of child abuse are mostly people who are known to the victim. The perpetrator's or subject's house is the place where most physical, emotional, or sexual violence occurs, which is 72.2%, 69.7%, and 89.7% respectively.Conclutions: Most cases of Child abuse occur in the age group of 13-15 years and 16-18 years. Child abuse is more common in women; most of the perpetrators are people who are recognized. Home is the most common place of physical, emotional, or sexual violence.